On the Solvability of Reaction-Diffusion COVID-19 Model with Variable Exponents - Sudha, Y.; Mani, V. N. Deiva; Anthoni, S. Marshal; Murugesan, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
One of the calamities in the health sector during the recent years is COVID-19(Coronavirus Disease - 2019). The COVID-19 pandemic not only leads to a health crisis but also an economic and social crisis. To retrieve from this situation, it is essential to study the mathematical model of COVID-19. In this paper, a reaction-diffusion COVID-19 model, is considered. The aim of this article is to prove that the considered reaction-diffusion system with variable exponents has a unique weak solution. By regularizing the considered system and by using Faedo-Galerkin method, compactness result, and Gronwall lemma the main objective of the paper is obtained.